Refractive Thinking in Solving Mathematical Problems in Indonesia: A Systematic Literature Review - Septian, Teddy; Juandi, Dadang (Universitas Wiralodra, 2023)
Refractive thinking is a thinking process that produces decisions through critical and reflective thinking. Refractive thinking focuses on critical thinking and problem-solving abilities. Both of these abilities are essential abilities in the 21st century that are needed by students. Research on refractive thinking in solving math problems has started to become a concern in the last 10 years. This study aims to describe the results of studies related to refractive thinking in solving math problems in Indonesia. This study used a Systematic Literature Review (SLR) method with a quantitative approach, involving 17 published studies as a sample which were filtered through inclusion criteria. This study took the stages of data collection, data analysis, and conclusions drawing. The results show that the research on refractive thinking in solving mathematical problems in Indonesia has been viewed from several aspects, most of these research show that students meet the indicators of refractive thinking on the component of identifying problems, and some of them show that students have not met the indicators on the strategy and evaluation components, and the use of Peer-Assisted Reflection learning models can improve mathematical refractive thinking abilities. Many of these studies involved junior high school students as participants because mathematical abilities begin to be honed at that level. In addition, the type of research most widely used is qualitative because this approach provides an in-depth understanding of refractive thinking in solving mathematical problems.